2000
DOI: 10.1053/jhep.2000.20237
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurring hepatocellular carcinoma differ according to infected hepatitis virus-An analysis of 236 consecutive patients with a single lesion

Abstract: Patients with hepatocellular carcinoma (HCC) frequently experience intrahepatic HCC recurrence even after complete ablation of primary lesions. Because the oncogenic process may be different for hepatitis B viral (B-viral) and hepatitis C viral (C-viral) HCC, the present study was conducted to elucidate the factors contributing to HCC recurrence with respect to the infected hepatitis virus. Two hundred thirty-six patients with a single HCC lesion who underwent complete ablation of the tumor by PEIT and/or PMCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 52 publications
(77 reference statements)
4
96
1
1
Order By: Relevance
“…RFA is successful for achieving a one-session treatment for patients with small HCC using RFA with CT assistance, and RFA with CT assistance is effective for the treatment of patients with small HCC [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . One of the advantages of RFA is that it can be repeatedly performed, can be combined with TACE, and can also be used according to the features of the disease and the response [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RFA is successful for achieving a one-session treatment for patients with small HCC using RFA with CT assistance, and RFA with CT assistance is effective for the treatment of patients with small HCC [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . One of the advantages of RFA is that it can be repeatedly performed, can be combined with TACE, and can also be used according to the features of the disease and the response [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the high level of serum ALT for 2 years or more were at a greater risk of HCC development [17] . Patients with HCV-associated cirrhosis with a sustained high serum ALT level are at a high risk of HCC development, suggesting the possibility of the prevention of HCC development in HCV-associated cirrhosis patients by reducing inflammatory necrosis [13] . Many investigators have shown that patients with cirrhosis who have persistently high ALT levels have a high risk of developing HCC [16,19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between clinicopathologic parameters and prognosis for patients with HCC has been studied widely, and several factors, such as IM through the portal vein, cirrhotic staging, pathologic grade, and serum ␣-fetoprotein levels, have been associated with a poor prognosis. 32,33 However, the molecular mechanism of metastasis and recurrence remains unclear. In our large-scale studies, obvious amplification differences between primary HCC and metastatic HCC were detected by the c-myc probe (29% vs. 45%) and the AIB1 probe (23% vs. 41%).…”
Section: Discussionmentioning
confidence: 99%
“…The rates of intrahepatic recurrence at 1, 3 and 5 years after radical treatment are reported to reach 19, 50 and 64%, respectively [8] and recurrent HCC is a major factor contributing to the poor prognosis. It is possible that some cases of intrahepatic recurrence are due to tiny nodules that cannot be detected by computed tomography (CT) at the time of initial diagnosis.…”
Section: Introductionmentioning
confidence: 99%